Biosynthesis of the Photosystem I Chlorophyll-Protein Complex in Greening Leaves of Higher Plants - Alberte, Randall S. (1973)
Biosynthesis of photosystem I chlorophyll-protein complex, derived from chloroplast lamellae solubilized with Triton X-100, was examined in rapidly greening primary leaves of the jack bean. It was found that the chlorophyll/P700 ratio of the complex was low (35/1) in the early stages of greening, and increased steadily to a stable level (75/1) during continued chloroplast development. It is suggested from these results that in the initial stages of greening, and probably throughout synthesis, the P700-chlorophyll-protein molecules are first inserted into the developing lamellae, and those photosystem I chlorophyll-protein molecules functioning solely in a light-harvesting capacity are added subsequently.